Increased IgA rheumatoid factor and VH1 associated cross reactive idiotype expression in patients with Lyme arthritis and neuroborreliosis. Issue 12 (1st December 1999) - Axford, John S; Rees, David H E; Mageed, Rizgar A; Wordsworth, Paul; Alavi, Azita; Steere, Allen C
Abstract : OBJECTIVE: To investigate whether autoreactive mechanisms occur in Lyme disease (LD) by determining IgA, IgG and IgM rheumatoid factor (RF) concentrations and RF associated cross reactive idiotype (CRI) expression in the serum of LD patients, with comparison to patients with rheumatoid arthritis (RA). METHODS: The RF isotype profiles were determined in 59 patients with LD; erythema migrans (EM) (n=19), neuroborreliosis (NB) (n=20) and Lyme arthritis (LA) (n=20). Mouse monoclonal antibodies (mAbs) G6 and G8 (VH 1 gene associated), D12 (VH 3 gene associated) and C7 (Vκ III gene associated) were then used to determine the RF associated CRI expression on IgM antibodies in 16 of these LD patients (eight seropositive for RF); (EM (n=3), NB (n=6), LA (n=7)). RESULTS: Seven (18%) patients with either NB or LA had increased concentrations of IgA RF compared with none with EM. Significant differences in the number of patients with raised concentrations of IgG RF or IgM RF were not found between the LD patient groups. Five (3NB, 1LA and 1 EM) (31%) and three (2NB and 1LA) (19%) of LD patients had raised concentrations of the CRIs recognised by mAbs G6 and G8, respectively. These CRIs were detected in LD sera both with and without raised concentrations of RF and were not demonstrated on anti-Borrelia burgdorferi antibodies using ELISA. No LD sera tested had raised concentrations of the determinants recognised by mAbs C7 or D12. CONCLUSION: Significantly raised concentrations of IgA RF and increased use of VH 1 germline gene associated CRIs are found on IgM antibodies in the serum of LD patients. These data indicate the recruitment of autoreactive B lymphocytes in some patients with the later stages of LD.